Hysteresis and electrode polarization in normal and inverted hybrid perovskite solar cells - Elumalai, Naveen Kumar; Mahmud, A.; Wang, D.; Wright, M.; Upama, M.; Chan, K.; Xu, C.; Uddin, A. (2018)
© 2017 IEEE. Organic-inorganic hybrid perovskite solar cells (PSCs) have demonstrated enormous potential to replace the traditional silicon photovoltaics. In spite of impressive progress, an in-depth understanding of various physiochemical and electronic properties of PSCs are yet to be unravelled. Anomalous hysteresis is one among them and its origin is a highly debated issue till date. In this work, the role of device structure and interfacial charge selective layer on the origin of hysteresis phenomenon was investigated. Normal devices with ZnO as electron transport layer exhibited excess interfacial capacitance in an order of magnitude higher than inverted devices with PCBM. Current-voltage characteristics correlated with capacitance measurements revealed that the electrode polarization as a consequence of ion migration and interfacial defect states might be a possible origin for hysteresis in PSCs.